Factors Affecting Farmers’ Participation In Participatory Irrigation Management In Tail-End Of The Uda Walawe Irrigation Scheme, Southern Sri Lanka - Darshanie Sewwandika Yapa, Loku Gamage (2022)
Participatory Irrigation Management (PIM) was introduced in the late 19th century as a type of irrigation reform for dealing with poor irrigation system performance in many agricultural areas of the world, including Sri Lanka. However, the emergence of head-tail disparity along the canal network has frequently resulted in inefficiency in irrigation management, causing this issue to become a subject of heated debate among scholars. Although some scholars have pointed out that an appropriate level of farmers’ participation is difficult to bring about at the tail-end of many irrigation schemes in Sri Lanka, no one has pinpointed the factors influencing the tailend farmers’ participation in PIM. Therefore, the objectives of the study are to assess the non-spatial, spatial, and overall factors that significantly affect tail-end farmers’ participation in PIM. The study was conducted at the tail-end of the Uda Walawe irrigation scheme, which remains as one of the perpetually water deficit schemes in Sri Lanka. Data were collected from 482 irrigated plots of cultivators by conducting a questionnaire survey, field observations and informal discussion. Apart from that, key informant interviews and focus group discussion were held with Irrigation Agency officers and farmer organization leaders to collect supplementary data and information related to the study. QGIS 3.16.6 and SPSS ver. 20.0 were used for digitizing, calculating, and analysing the collected data. The study revealed that 59% of the total number of farmers at the tail-end of the scheme actively engaged in collective action while 41% were inactive in PIM.